(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
Grammar takes a big area in teaching English and the concept grammar is still controversial to teachers and learners in Iraq. Many causes rise this dilemma : first Arabic grammar and techniques of teaching it as well as teachers` point of view toward grammar. Second, students` attitudes about Arabic grammar and their techniques to deal with English grammar. Methods of teaching and development in teaching and other fields that effect teaching process gave a variety of methods and producers to present grammar in class. So, some teachers in Iraq support traditional methods and some reject them and begin to talk about CLT for example as and this makes them to face another problem which is where and when we present grammar and which grammar is suitable and enables students to develop their language